Subnational institutions and open innovation: evidence from China - Sun, Fei; Hong, Junjie; Ma, Xiuying; Wang, Chengqi (Emerald, 2017)
Purpose: The purpose of this paper is to examine how subnational institutions within a country explain the performance consequences of open innovation (OI) in emerging market enterprises (EMEs). Design/methodology/approach: The paper conducts a regression analysis by using a novel panel data set comprising of 438 innovative Chinese firms over the period of 2008-2011. Findings: The authors show that although on average openness to external actors improves innovation performance this effect is pronounced for EMEs that operate in subnational regions with a higher level of intellectual property rights (IPR) enforcement and of factor market development. The findings point to the context-dependent nature of OI strategy and the complementary effect of institutional parameters in emerging markets and help to reconcile the contrasting findings regarding the effect of OI in the prior literature. Originality/value: This paper extends the literature on OI by suggesting that the analysis of the performance consequences of OI strategy should go beyond the nexus between OI and firm performance, and instead, focus on subnational-specific institutions, such as region-specific IPR enforcement, factor market development and intermediation market development, that may facilitate or constrain the effect of OI model.